Modelling of the Elementary Steps Involved in the Aluminum Electrochemical Deposition from Ionic Liquid Based Solution: The BMImCl/AlCl3 System. Issue 1 (1st January 2020) - Innocenti, Massimo; Giaccherini, Andrea; Chelli, Riccardo; Martinuzzi, Stefano; Giurlani, Walter; Passaponti, Maurizio; Lavacchi, Alessandro; Fontanesi, Claudio
Abstract : The energy hierarchy, of the main chemical species involved in the reaction mechanism relevant to the electrodeposition of aluminum in 1-Butyl-3-methylimidazolium chloride/aluminum trichloride solution ( BMImCl / AlCl 3 ), is studied by using ab-initio based theoretical calculations. Eventually, a reasonable theoretical estimate of energies, involved in the principal reactions ruling the aluminum electrodeposition from BMImCl ionic liquid solutions, is obtained. For screening purposes (geometry optimization and Hessian calculations) the CAMB3LYP density functional, DFT, has been used. Then single point (exploiting CAMB3LYP optimized geometries) energy data are obtained at the Møller-Plesset (MP2) level of the theory. They are used to cross-check DFT results. A reaction mechanism emerges in which, although the species AlCl − 4 is formed with very high efficiency from the neutral species AlCl 3, the competing reaction A l C l 4 − + A l C l 3 ⇌ A l 2 C l 7 − points to an almost complete conversion of aluminum to the dimeric form into bulk solution. This is observed in the absence and, most importantly, in the presence of a coordinating BMIm + cation. In this respect, the presence of BMIm + does not seem to affect significantly the equilibrium between the monomeric and dimeric forms of aluminum. This outcome is very interesting because the dimeric species is directly reduced to yield the metal aluminum. Indeed, a larger concentration of Al 2 Cl − 7 gives due reason for a more effective electrodeposition process, as it is experimentally observed in the ionic liquid medium.